COSMITTO: Document Management System - Sambrano, Jasmin; Dirain, Estela (Studies in Technology and Education, 2026)
The developed COSMITTO: Document Management System is necessary due to the increasing quantity of digital documents and the challenges associated with inefficient, manual document handling in Cagayan State University – Aparri Campus. The general objective of this study was to design, implement, and assess COSMITTO System, particularly for the Office of the Campus Executive Officer of CSU-Aparri, to improve the efficiency and accessibility of document management. The study employed an Agile Development Methodology, utilizing PHP, MySQL, and JavaScript, with evaluation conducted by 23 faculty and personnel selected through purposive sampling. The primary tool for evaluation was the ISO 25010:2023 standard, focusing on functional suitability and performance efficiency. The results showed that end-users are satisfied with the COSMITTO System with both functional and non-functional parts, demonstrating significant improvements in processing time and user satisfaction compared to the existing manual system. It was concluded that COSMITTO is highly acceptable, reliable, and addresses the critical documentation bottlenecks. The primary recommendation is for the campus to adopt and integrate COSMITTO to establish a standardized, campus-wide digital document management, with mandatory user training to ensure system integration and adoption.